2021
DOI: 10.3389/fcell.2021.740783
|View full text |Cite
|
Sign up to set email alerts
|

To B (Bone Morphogenic Protein-2) or Not to B (Bone Morphogenic Protein-2): Mesenchymal Stem Cells May Explain the Protein’s Role in Osteosarcomagenesis

Abstract: Osteosarcoma (OS), a primary malignant bone tumor, stems from bone marrow-derived mesenchymal stem cells (BMSCs) and/or committed osteoblast precursors. Distant metastases, in particular pulmonary and skeletal metastases, are common in patients with OS. Moreover, extensive resection of the primary tumor and bone metastases usually leads to bone defects in these patients. Bone morphogenic protein-2 (BMP-2) has been widely applied in bone regeneration with the rationale that BMP-2 promotes osteoblastic different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 161 publications
(173 reference statements)
0
2
0
Order By: Relevance
“…First, based on bulk RNA results, we focused on osteogenic-related expression among tumor cells ( Figure 4B ). Osteosarcomagenesis has been reported to be closely associated with the osteoblastic lineage and shows osteogenic differentiation-related activity in proliferation, ECM secretion and ossification induction ( 25 , 26 ). We noticed that C11, C18 and C38 strongly upregulated proliferative expression, including DNA replication, chromosome organization and miotic expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, based on bulk RNA results, we focused on osteogenic-related expression among tumor cells ( Figure 4B ). Osteosarcomagenesis has been reported to be closely associated with the osteoblastic lineage and shows osteogenic differentiation-related activity in proliferation, ECM secretion and ossification induction ( 25 , 26 ). We noticed that C11, C18 and C38 strongly upregulated proliferative expression, including DNA replication, chromosome organization and miotic expression.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we noticed that the transmission came through upregulating osteoblastic differentiation-like expression. Studies have revealed that osteoblastic differentiation is closely associated with osteosarcoma tumorigenesis ( 25 , 26 ). This result supported the osteogenic CSC roles of C14 and C25.…”
Section: Discussionmentioning
confidence: 99%